2016
DOI: 10.2135/cropsci2015.04.0260
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Marker × Environment Interaction Model for Genomic‐Enabled Prediction and Genome‐Wide Association Analysis in Durum Wheat

Abstract: 2193RESEARCH G enetic ´ environment interaction (G´E) affects trait heritability and the relative rankings of phenotypes across environments; this introduces challenges when making breeding decisions. The effects of G´E on heritability may be due to scale effects such as changes in the size of quantitative trait loci (QTL) effects across environments or to differential genetic effects on environmental variance. However, G´E can also modulate QTL effects, thus introducing changes in the relative rank of genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 37 publications
(64 reference statements)
13
96
0
Order By: Relevance
“…This CV2 validation strategy performed better than CV strategy CV1 (where lines have not been evaluated in any field trials) proposed by Burgueño et al (2012), when applied in multi-environment models (Jarquín et al 2014; López-Cruz et al 2015; Crossa et al 2016b; Saint Pierre et al 2016). …”
Section: Discussionmentioning
confidence: 84%
“…This CV2 validation strategy performed better than CV strategy CV1 (where lines have not been evaluated in any field trials) proposed by Burgueño et al (2012), when applied in multi-environment models (Jarquín et al 2014; López-Cruz et al 2015; Crossa et al 2016b; Saint Pierre et al 2016). …”
Section: Discussionmentioning
confidence: 84%
“…The prediction of individual trials or locations across years is an especially difficult task (Dawson et al 2013) and we observed a large variation in prediction accuracy for this undertaking in our study (Fig S3), fitting the results of other studies with autogamous crops (Heslot et al 2014; Lado et al 2016). Once multi-environment trials are being conducted, more options open up for enhancing the selection of variety parents like imputing untested lines in tested locations (Burgueño et al 2011; Jarquín et al 2014; Crossa et al 2016; Lopez-Cruz et al 2015) or enhancing the reliability of breeding values by a relationship matrix (Bauer et al 2006; Oakey et al 2007b; Bauer et al 2009; Müller et al 2015). Hence, predicting lines for the entire target population of environments might be a better strategy to select candidates that should enter multi-environment trials.…”
Section: Discussionmentioning
confidence: 99%
“…The marker × environment interaction model has some advantages over previous models: it is easy to implement in standard software for GS and can be implemented with any Bayesian priors commonly used in GS, including not only shrinkage methods ( e.g. , GBLUP), but also variable selection methods (which cannot be directly implemented under the reaction norm model) (Crossa et al 2016). …”
mentioning
confidence: 99%